Penggunaan Metode Kontrasepsi Susuk KB di Jawa Timur (Analisis Data SUSENAS 2015) - Monita Destiwi (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
One of the problems being faced by Indonesia is the population explosion. The increasing population is a result of the increasing birth rate. To lower thebirth rate the use of long acting contraceptive methods is being promoted. Based on data from SDKI 2012, the percentage of the the use of contraceptives in East Java is still dominated by the use of short acting contraceptive methods (80.99 percent). Meanwhile the long acting contraceptive methods are still lacking in use. One type of long acting contraceptive methods is implant. This study is aimed at exploring the factors that influence the use of implants in the East Java Province based on data from SUSENAS 2015. This is a non-reactive study which used a secondary data analysis with a cross-sectional design. The sample was taken from the data of female respondents of SUSENAS 2015 who were 15–49 years old, used implant methods and lived in East Java. Chi square test and logistic regression were used to analyze the data.The results showed that women who were 30 years of age or older (OR = 3.653), had at least three children (OR = 2.563) and had previous experinces with modern contraceptives (OR = 0.109) affected the use of contraceptive implant methods in East Java. It is expected that by conducting education and socialization on the use of contraceptive implants for family planning to couples at reproductive ages, the use of contraceptive implants can be more optimized.